ATURAN KAMPANYE PEJABAT NEGARA DALAM UNDANG- UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM MENURUT PERSPEKTIF FIQH SIYASAH DUSTURIYAH - Rike Sukma Wadhoni; Edi Yuhermansyah; Riadhus Sholihin (Journal of Indonesian Comparative of Syari'ah Law, 2025)
Many incumbent officials continue to exploit state facilities such as official vehicles, government housing, and even involve civil servants in covert campaign activities, even though it's forbidden. This study aims to analyze the legal provisions regarding state officials’ campaigns under Law No. 7 of 2017 through the lens of fiqh siyasah dusturiyah (Islamic constitutional politics). The analysis focuses on aligning positive legal norms with Islamicvalues such as justice (al-‘adālah), trustworthiness (al-amānah), and public interest (maslahah ‘āmmah) as ethical standards inpolitics. The study uses a normative-qualitative method by examining academic literature, legal regulations, and classical Islamic texts. The findings of this study indicate that, from a normative perspective, the provisions in Law No. 7 of 2017 firmly prohibit the use of state facilities for campaign purposes. However, when compared with the values of fiqh siyasah dusturiyyah, it is evident that these provisions do not fully reflect the principles of al-ʿadālah (justice), al-amānah (integrity), and maṣlaḥah ʿāmmah (public interest), as they lack a moral foundation and ethical oversight grounded in Islamic spirituality.